Android-Based Mathematics Learning Application with Elements of Etnomathematic Sundanese Traditional Games - Wanti Rahayu; Ari Irawan; Rahnita Nuzulah (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
This research aims to create an Android-based mathematics learning application using ethnomaematic elements in traditional Sundanese games. The method used is RnD (Research and Development) with the Borg and Gall model. As for the Borg and Gall model, there are 10 stages of implementing the development of this Android-based mobile learning learning media, namely 1) potential problems; 2) data collection; 3) product design; 4) design validation; 5) revision 1; 6) product trial; 7) revision 2; 8) trial use; 9) revision 3; 10) mass production. Based on the research stages with the Borg and Gall approach, not all have been passed. This research was conducted for two years, now is the first year so that the new stage is design validation carried out by two validators, namely media and materials. The result of this research is an application for learning mathematics with an ethnomathematical approach to traditional Sundanese games based on Android which is still only at the validation stage of media and material experts. Keywords: Mathematics Learning Applications, Android Math, Ethnomaematic, Sundanese Traditional Games.